The role of brand attachment and its antecedents in brand equity in Higher Education: an extended abstract - Dennis, Charles; Papagiannidis, Savvas; Alamanos, Eleftherios; Bourlakis, Michael (Springer, 2017)
In an increasingly competitive higher education sector, universities face significant challenges when it comes to recruiting new students. Recruitment is only the beginning of a long-term relationship that higher education institutions (HEI) need to cultivate, not only while students attend the programs, but also beyond graduation. Previous studies highlight the need for research in relation to the power that comes from successful branding and the implications for HEIs (Dholakia and Acciardo 2014). This paper aims to contribute to an underdeveloped area in the literature related to brand attributes and their importance in the context of the higher education sector (Chapleo 2010). Specifically, the research objective is to examine the influence of HEIs’ brand identity, brand meaning, and brand image on brand equity as a result of forming strong attachment, commitment, trust and overall satisfaction from the vantage points of students and graduates; representing major research gaps identified in contemporary literature. Specifically, the first main aim of this work is to investigate whether universities’ positioning strategies should continue focusing on building prestige or whether strategies aimed at improving student satisfaction could have more positive effects on brand equity. The second aim of this work is to examine whether the perceived by the students brand equity of an institution is different for students and graduates. The third main aim of the paper is to examine the relationship between attachment strength and satisfaction.